Pharmacological Studies on Fullerene (C60), a Novel Carbon Allotrope, and Its Derivatives - Mitsutoshi Satoh; Issei Takayanagi (Elsevier, 2006)
Abstract.: Fullerene (C60), a condensed ring aromatic compound with extended π systems, is a novel carbon allotrope. Because of its poor solubility in polar solvents, investigation of the biological and pharmacological properties of fullerene has been difficult. Recently, water-soluble fullerene derivatives have been synthesized, and we and others have found that they have potent and selective pharmacological effects on organs, cells, enzymes, and nucleic acids. In the presence of fullerene C60 derivative (10−5 M), endothelium-dependent relaxations induced by agonists in the vascular system were eliminated and acetylcholine-induced contractile response of smooth muscle was observed. Some investigators have reported free radical-scavenging activity and direct nitric oxide-quenching activity of fullerene derivatives. Knowledge of the chemical modifications, biological significance, and materials applications of functionalized fullerenes is growing rapidly; and these compounds are emerging as new tools in the field. The focus of this review is to introduce several pharmacological effects of fullerenes and to discuss the possible mechanisms of the pharmacological actions caused by previously synthesized fullerenes. Keywords:: fullerene C60 derivative, nitric oxide, smooth muscle, nerve protection, anti-tumor